Spiral field generation in Smith-Purcell radiation by helical metagratings - Jing, Liqiao (2020)
Moving electrons interacting with media can give rise to electromagnetic radiations and has been emerged as a promising platform for particle detection, spectroscopies, and free-electron lasers. In this letter, we investigate the Smith-Purcell radiation from helical metagratings, chiral structures similar to deoxyribonucleic acid (DNA), in order to understand the interplay between electrons, photons, and object chirality. Spiral field patterns can be generated while introducing a gradient azimuthal phase distribution to the induced electric dipole array at the cylindrical interface. Experimental measurements show efficient control over angular momentum of the radiated field at microwave regime, utilizing a phased electromagnetic dipole array to mimic moving charged particles. The angular momentum of the radiated wave is determined solely by the handedness of the helical structure, and it thus serves as a potential candidate for the detection of chiral objects. Our findings not only pave a way for design of orbital angular momentum free-electron lasers but also provide a platform to study the interplay between swift electrons with chiral objects.